Efficacy and safety of iron-chelation therapy with deferoxamine, deferiprone, and deferasirox for the treatment of iron-loaded patients with nontransfusion-dependent thalassemia syndromes - Taher AT; Porter JB; Kattamis A; Viprakasit V; Cappellini MD (Dove Medical Press, 2016)
Ali T Taher,1 John B Porter,2 Antonis Kattamis,3 Vip Viprakasit,4 M Domenica Cappellini51Department of Internal Medicine, American University of Beirut, Beirut, Lebanon; 2Department of Haematology, University College London, London, UK; 3First Department of Pediatrics, University of Athens, Athens, Greece; 4Department of Pediatrics and Thalassemia Center, Siriraj Hospital, Mahidol University, Bangkok, Thailand; 5Department of Internal Medicine, Università di Milano, Ca Granda Foundation IRCCS, Milan, ItalyAs the scientific steering committee for THALASSA (an assessment of Exjade in nontransfusion-dependent thalassemia [NTDT]), we read with interest the review by Kontoghiorghe and Kontoghiorghes entitled “Efficacy and safety of iron-chelation therapy with deferoxamine, deferiprone, and deferasirox for the treatment of iron-loaded patients with non-transfusion-dependent thalassemia syndromes” published in January 2016.1 While this review provides a detailed overview of available iron chelators for the treatment of NTDT patients, there remain some factual inaccuracies and misrepresentations of data related to deferasirox. Therefore, we believe that the current article may be misleading to readers of Drug Design, Development and Therapy.Author’s replyGeorge J KontoghiorghesPostgraduate Research Institute of Science, Technology, Environment and Medicine, Limassol, CyprusThere are many murky areas and marketing, legal, ethical, and other conflicts in the pharmaceutical industry, some of which involve physicians and academics. These activities and related ethical issues affect the safety and treatment of millions of patients.1–11 Irregular and sometimes illegal activities for new patented drugs carried out by pharmaceutical companies, such as secrecy agreements with academics/academic institutions, can lead to biased reporting of the results of clinical trials and cover ups or underreporting of toxic side effects, as well as doctor’s bribes, irregularities in drug pricing, corruption of the drug regulatory authorities, influential medical journals and patient organizations, etc.1–11 The commercial influence and drug marketing tactics by pharmaceutical companies in the case of deferasirox affect the safety and long-term survival of thousands of thalassemia and other categories of transfused patients.11–14View the original paper by Kontoghiorghe and Kontoghiorghes.